2019
DOI: 10.1515/ijnes-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Practicums Conducted in School Settings: An Integrative Review

Abstract: BackgroundExamining nursing pedagogical strategies is important to assure that nursing students have opportunities to become knowledgeable and skilled clinicians. However, little is known about the nursing pedagogical strategy of using schools for pediatric practicum. The purpose of this review is to integrate the evidence regarding the use of schools as practicum sites for nursing students to obtain pediatric clinical experience.MethodSearches were conducted in three electronic databases resulting in 70 publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Innovative sites beyond the hospital for pediatric clinical practicum24 are needed to provide students with opportunities gain competencies to care for children. In this era of dwindling clinical sites, as well as the critical need to prepare and maintain a pediatric nursing workforce,25 elementary, middle, and high school settings offer fertile grounds for learning about pediatric nursing 7. In addition, learning about content such as pediatrics is enhanced when the experience occurs within a setting26 specifically intended for children that involves their parent(s).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Innovative sites beyond the hospital for pediatric clinical practicum24 are needed to provide students with opportunities gain competencies to care for children. In this era of dwindling clinical sites, as well as the critical need to prepare and maintain a pediatric nursing workforce,25 elementary, middle, and high school settings offer fertile grounds for learning about pediatric nursing 7. In addition, learning about content such as pediatrics is enhanced when the experience occurs within a setting26 specifically intended for children that involves their parent(s).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical frameworks used to guide practicums in this study differed from service learning and experiential models previously identified in the literature. 7 The use of frameworks or theoretical models helps guide curricular design and provides consistency in subsequent course development and implementation. Interestingly, curricular frameworks are no longer required for accreditation but are implied in accrediting standards.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations